Analisis User Acceptance Pada Aplikasi Layanan Kesehatan Online di Jawa Tengah dan Daerah Istimewa Yogyakarta - Magus Sediono; Sri Kusumadewi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The variety of health information through the internet (Health Information System/HIS) can increase knowledges, competences, and patient’s involvement in health decision making strategies. The analysis of user acceptance related to the different perspectives of users of health information services has not been given much attention. Therefore, this study aims to determine the effect of user experience and service quality on user acceptance in online health service applications. A total of 102 respondents who are health practitioners (clinics) in the Province of Central Java and the Special Region of Yogyakarta were included in this study. The results showed that user experience and service quality in the group of physicians had a positive effect on user acceptance (Sig. <0.05). In addition, these two variables contribute 75.2% to user acceptance of online health service applications. However, for nurse clinicians, user acceptance is only influenced by user experience. The relationship between the three variables looks strong with a unidirectional correlation. Thus, increasing user experience and service quality in online health service applications will result in increased user acceptance.